Beyond the 9-to-5: Unravelling the Pros and Cons of Moonlighting in Today’s Job Market (Journal of Informatics Education and Research, 2024)
In current years, moonlighting, defined as the practice of performing multiple tasks simultaneously, has gained prominence as an integral part of the evolving business environment. The first section explains the meaning and theoretical basis of moonlight. We explore its historical background, legal implications, and impact on employee well-being through established research. The second section focuses on our research methodology, highlighting the data selection criteria included in this study, which are carefully detailed. Strong research practices ensure the accuracy of our findings. The third category classifies motivations for moonlight behaviour. From economic incentives to personal preferences, we explore why individuals choose to balance multiple roles. The fourth section includes sector-specific research that sheds light on broad moonlighting across sectors. We explore how moonlight and gig economy trends align with traditional employment models. The relationship between moonlighting and organizational commitment is explored in Section V. We examine whether moonlighting affects loyalty, participation, and performance in an employee’s primary job.Our paper concludes by summarizing the main takeaways and proposing avenues for future research. Moonlighting is a multifaceted phenomenon, and understanding its implications is critical for employees and employers alike.This study contributes to the ongoing discourse on career mobility, and provides insights for policy makers, HR professionals, and scholars alike. As organizations adapt to the changing landscape, acknowledging and addressing moonlighting practices becomes essential for sustainable workforce management.